PROBABILISTIC ANALYSIS OF DEPTH AND CARBONATION FRONT DEVELOPMENT IN CONCRETE OF MARINE STRUCTURES - E. E. Shalyi; L. V. Kim; S. N. Leonovich; A. V. Stepanova; Е. Е. Шалый; Л. В. Ким; С. Н. Леонович; А. В. Степанова (Science & Technique, 2018)
On the coast of the Russian Far East the climate is monsoon, which is most pro-nounced in the south and northeast waning. Seasonal change of oceanic and continental influence is reflected in the nature of the climate: summer is moderatelywarm and rainy, winter is cold and snowy. On Sakhalin winters are less severe than on the mainland. In Kamchatka, where the winters are milder, the influence of the continental monsoon less. In the southern part of Primorye snow is so small that there is in the rivers spring flood. In the north of the Amur region, Sakhalin, Kamchatka rainfall and snowpack increases. In the summer is dominated by southeast wind, which spread to the continent moist Pacific air. During the year, between the Pacific Ocean and the south of the Far East there is an intensive exchange of air masses. Seasonal change of air currents is determined by the thermal contrast between the continent and the ocean. During the year passes over the area to an average of 100 cyclones (3–6 per month during the cold period, and up to 3 – warm), which are ac-companied by increased wind, cloudy weather with precipitation, and in late summer and early au-tumn, typhoons observed outputs. Typhoons are accompanied by stormy winds reaching speeds of over 40 m / sec. and heavy rains. A wide variety of observed in the distribution of precipitation. The Chukchi-Anadyr area for the warm period falls to 200–250 mm in the north of the Sea of Okhotsk – 400–500 mm, in intermountain basins up to 250–300 mm. To the south the amount of precipitation increases to 500 to 600 mm in the Amur region and 900–1000 mm on the western slopes of Sikhote Alin. In the course of the annual maximum rainfall in the second half of the summer, but there are rainy June and September. No wonder that in such conditions, corrosion, material of hydraulic structures is most intense. Concrete and cement stone reinforced concrete structures exposed to corrosive attack, particularly the aggressive action of CO2 common acid gas, which is to neutralize the surface ...